WHAT IS THE ROLE OF MEDIA IN SHAPING CULTURAL IDENTITIES AND VALUES? - Sattorova Mavluda; Fozilbek Orzibekov (TADQIQOTLAR, 2025)
Abstract The media plays a crucial role in shaping cultural identities and values by  influencing  perceptions,  behaviors,  and  social  norms.  Through  various  forms, including television, film, social media, and news outlets, media serves as a powerful tool for disseminating cultural narratives, reinforcing traditions, and introducing new perspectives.  It  contributes  to  identity  formation  by  portraying  cultural  symbols, historical events, and societal expectations, which help individuals develop a sense of belonging. Additionally, globalization has expanded media's influence, leading to the blending of cultures while also raising concerns about cultural homogenization. While media  fosters  cross-cultural  understanding  and  appreciation,  it  can  also  reinforce stereotypes and biases. Therefore, its role in shaping cultural identities requires critical engagement to promote inclusivity and authenticity. This paper explores how media influences  cultural  identities  and  values,  examining  both  its  positive  and  negative impacts on society.